2005
DOI: 10.1016/j.cub.2005.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Drosophila DJ-1 in Survival of Dopaminergic Neurons and Oxidative Stress

Abstract: The loss of dopaminergic neurons in the substantia nigra is the pathological hallmark of Parkinson's disease (PD). While the etiology of sporadic PD remains elusive, an inherited form of early-onset familial PD is linked to mutations of DJ-1. To understand the biological function of DJ-1 and its relevance to the pathogenesis of PD, we investigated the function of DJ-1 using Drosophila. Drosophila possesses two homologs of human DJ-1: DJ-1alpha and DJ-1beta. We found that DJ-1alpha is expressed predominantly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
141
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(151 citation statements)
references
References 13 publications
7
141
0
3
Order By: Relevance
“…Alternatively, PINK1 could functionally collaborate with parkin and DJ-1, two other recessive, early-onset PD-linked genes, to regulate neuronal sensitivity to oxidative stress. In vitro, parkin and DJ-1 have been shown to protect cells from oxidative stress (26)(27)(28)(29)(30)(31). Moreover, PINK1 interacts with DJ-1 and digenic mutations of PINK1 and DJ-1 are associated in early onset familial form of PD (15).…”
Section: Aј-dј and E)mentioning
confidence: 99%
“…Alternatively, PINK1 could functionally collaborate with parkin and DJ-1, two other recessive, early-onset PD-linked genes, to regulate neuronal sensitivity to oxidative stress. In vitro, parkin and DJ-1 have been shown to protect cells from oxidative stress (26)(27)(28)(29)(30)(31). Moreover, PINK1 interacts with DJ-1 and digenic mutations of PINK1 and DJ-1 are associated in early onset familial form of PD (15).…”
Section: Aј-dј and E)mentioning
confidence: 99%
“…The DJ-1 protein responds to oxidative stress evidenced by a pI shift in sporadic PD (4,5) and in cell (6,7) and animal (8) models. DJ-1 knockout models also show increased sensitivity to toxins that cause mitochondrial dysfunction or oxidative stress (9)(10)(11)(12)(13). Cys-106 of DJ-1, which is oxidized to form a cysteine-sulfinic acid, is critically required for DJ-1 to protect against these types of damage both in vitro (6) and in vivo (12).…”
mentioning
confidence: 99%
“…DJ-1 is conserved in bacteria, plants, animals, and humans (Lucas and Marin, 2007). It is well known that DJ-1 has multiple functions including anti-oxidant and chaperone functions associated with PD pathogenesis (Menzies et al, 2005;Xu et al, 2005;Zhou et al, 2006). However, DJ-1 deficiency or loss-of-function leads to oxidative stressinduced cell death in vitro and in vivo (Chen et al, 2005;Goldberg et al, 2005;Kim et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have demonstrated that DJ-1 protein protects against neuronal cell death resulting from 6-OHDA-induced ROS. After exposure to dopaminergic neurotoxins including rotenone and 6-OHDA, intracellular ROS levels were inversely correlated with DJ-1 expression levels, suggesting that DJ-1 may mitigate 6-OHDA-induced oxidative stress and help protect cells against oxidative stress (Menzies et al, 2005;Xu et al, 2005;Zhou et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation